Accountability Strategy for Reporting Village Fund Management - Andi Abubakar; Muslimin Muslimin; M. Awaluddin A; Feby Triadi; Hezron Alhim Dos Santos (Jurnal Ad'ministrare, 2023)
Consequences in implementing Law no. 32 of 2004 of course also has an impact on implementation at the village government level, which in article 206 is regarding government affairs which are the authority of the village. This research is about village funds sourced from the district/city APBN budget which are channeled to support village improvement which includes governance, development implementation, guidance and empowerment. Along with this, community concerns also arise regarding the accountability, quality and effectiveness of Village Fund management which is often considered less effective. Law Number 6 of 2014 concerning Villages provides a strong basic foundation regarding the implementation of village government. Meanwhile, the research approach is qualitative - descriptive, emphasizing the results of interview data analysis, observation and also literature reviews. Since 2015, villages in Indonesia have received funding from the State Revenue and Expenditure Budget. Thus, each village is required to be accountable for managing village funds to the community. This research aims to evaluate the availability of adequate information regarding the use of Village Funds including the determination of the APBD and the extent of community knowledge regarding village government administration. This research uses qualitative data analysis by connecting one source with other sources, then drawing conclusions at various stages. This research found that the increasing public trust in village government and increasing community participation in village development means that village funds have become a means of providing trust for village administrators and the apparatus within them.